2009
DOI: 10.1538/expanim.58.181
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia and Hyperinsulinemia in the Spontaneous Osteoarthritis Mouse Model, STR/Ort

Abstract: Recent studies have focused on the association between primary osteoarthritis and dyslipidemia. STR/Ort mice have unique characteristics including osteoarthritis and hyperlipidemia, and may be a useful model for investigating the effect of dyslipidemia on the underlying mechanism of primary osteoarthritis. However, little is known about the hyperlipidemic properties of STR/Ort mice. In this study we investigated hyperlipidemia and lipotoxicity in STR/Ort mice. STR/Ort mice have human hyperlipidemic patient-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…According to this, the spontaneous osteoarthritis murine model (STR/Ort) also has low adiponectin levels associated with obesity (103). Both findings are in agreement with the already known inverse relationship between fat mass and adiponectin circulating levels.…”
Section: Adiponectin and Rheumatic Diseasessupporting
confidence: 88%
“…According to this, the spontaneous osteoarthritis murine model (STR/Ort) also has low adiponectin levels associated with obesity (103). Both findings are in agreement with the already known inverse relationship between fat mass and adiponectin circulating levels.…”
Section: Adiponectin and Rheumatic Diseasessupporting
confidence: 88%
“…moreover, Str mice exhibit hypercholesterolemia, hypertriglyceridemia, hyperinsulinemia, insulin resistance, dysregulation of nonesterified fatty acids and low serum adiponectin, as in human hyperlipidemic patients. thus, Str mice can be used as a model for investigating the involvement of dyslipidemia in the underlying mechanism for Oa (12).…”
Section: Discussionmentioning
confidence: 99%
“…in Str mice, visceral fat is accumulated in their peritoneal cavities and they are slightly obese. moreover, Str mice exhibit human hyperlipidemic patient-like symptoms, such as hypercholesterolemia, hypertriglyceridemia, hyperinsulinemia, insulin resistance, dysregulation of nonesterified fatty acids and low serum adiponectin (12).…”
Section: Introductionmentioning
confidence: 99%
“…The serum concentrations of glucose, total cholesterol, and triglyceride were assayed using LabAssay (TM) Series kits (Wako Pure Chemical Industries, Ltd, Osaka, Japan) and the serum concentration of insulin was determined using an insulin measurement kit (Morinaga Pharmaceutical Co., Ltd, Tokyo, Japan) (Uchida 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have focused on the association of altered bone and cartilage metabolism with metabolic factors such as cholesterol, triglycerides, glucose and adiponectin (Chen 2006;Kratnov 2006;Gomez 2009); however, the effects of these factors on the underlying mechanism of primary osteoarthritis are unknown. We previously identified that STR/Ort mice display human hyperlipidaemialike symptoms, including high serum total cholesterol, high serum triglycerides, and hyperinsulinaemia (Uchida 2009). Gaining a better understanding of the pathology of hyperinsulinaemia in STR/Ort may, therefore, reveal the relationship between OA, hyperinsulinaemia, and abnormal lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%